61 Temporal trends in the frequency of inducible myocardial ischaemia during single-photon emission computed tomography (SPECT): 2012–2017. (16th October 2019) - Kerley, R; Sharif, Z; Kearney, P
Abstract : Background: Recent large-scale studies have observed a gradual decline in the prevalence of abnormal single-photon emission computed tomography (SPECT) myocardial perfusion imaging (MPI) studies. The declining frequency and severity of myocardial ischaemia may reflect a broader temporal change toward milder presentations of coronary artery disease (CAD). Our aim was to assess the frequency of test abnormality and inducible myocardial ischaemia over the past five years at our Tertiary Academic Centre. Methods: Consecutive patients undergoing stress-rest MPI between 2012 and 2017 were identified in a retrospective observational analysis. We included both internal and external referrals for scans performed at Cork University Hospital. Patients were assessed for change in demographics, clinical symptoms, risk factors and frequency of abnormal and ischaemic SPECT-MPI. Results: Annual utilisation of stress-rest MPI at our tertiary care centre increased by 26.7% from 101 studies in 2012 to 128 in 2017. There was a progressive decline in the prevalence of abnormal stress-rest MPI studies from 34.7% in 2012 to 26.9% in 2017 although this did not reach statistical significance (p=0.391). Similarly, the prevalence of ischaemic stress-rest MPI declined, from 22.8% to 18.0% (p=0.408) with a non-significant increase in severe ischaemic detection (3.0% vs. 5.5%, p=0.519). Conversely, there was a progressive increase in the prevalence of hypertension (43.6% vs. 79.7%, p<0.001) and dyslipidaemia (37.9% vs. 59.4%, p<0.001) in patients undergoing stress-rest MPI imaging from 2012 to 2017. The prevalence of abnormal studies increased with the presence of hypertension (p<0.05), dyslipidaemia (p<0.001) and typical angina (p<0.05). Referral of patients with typical angina did not differ significantly from 2012 to 2017. All studies in our centre were performed using pharmacological stress testing most commonly adenosine (96.6%). Conclusion: Over the past five years, the frequency and severity of abnormal stress-rest MPI studies has progressively declined. Notably, the frequency of abnormal stress-rest MPI is now very low among patients without typical angina and known cardiac risk factors. These findings suggest the need for developing alternative strategies for evaluating patients who present with a low risk of manifesting inducible myocardial ischaemia during cardiac imaging procedures.